DIGITALISASI KITAB KUNING: ANALISIS DAMPAK APLIKASI FIKIH DIGITAL TERHADAP OTORITAS KEILMUAN PESANTREN - Muhammad Abraar (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the impact of digitizing kitab kuning (classical Islamic texts) through the emergence of digital fiqh applications on religious authority within pesantren environments. Employing a qualitative approach and case study method, this research was conducted in five prominent pesantren in Indonesia: Tebuireng, Lirboyo, Sidogiri, Gontor, and Al-Falah Ploso. Data collection techniques included in-depth interviews with 15 informants senior kyai, ustadz, and active students as well as participatory observation of the usage of apps like Laduni, Taqsim, and Fikih Muamalah. The findings reveal a disruption of traditional scholarly authority, particularly the role of kyai and the system of sanad (knowledge transmission chains). Many students increasingly rely on digital applications rather than direct guidance from their teachers. However, digitalization also brings positive impacts, such as broader access to classical references, time efficiency in bahtsul masail (legal discussions), and a growing interest in reading traditional Islamic texts. The study also highlights the rise of “digital ustadz” who gain scholarly legitimacy without formal pesantren education. Strategic measures from pesantren institutions and the Ministry of Religious Affairs are needed to develop their own digital platforms and regulate fiqh content to preserve the traditional values of Islamic scholarship.